JET FRAGMENTATION AND QCD MODELS IN EPSILON+EPSILON- ANNIHILATION AT CM ENERGIES BETWEEN 12.0 AND 41.5 GEV - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Bock, B; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; et al. (Springer-Verlag, 1988)
The large amount of data accumulated by the TASSO detector at 35 GeV c.m. energy has been compared with the predictions of the latest generation of perturbative QCD+fragmentation models. By adjustment of the arbitrary parameters of these models, a very good description of the global properties of hadronic events was obtained. No one model gave the best description of all features of the data, each model being better than the others for some observables and worse in other quantities. We interpret these results in terms of the underlying QCD and hadronisation schemes. The trends of the data across the energy range 12.0≦W≦41.5 GeV are generally well reproduced by the models with the parameters optimised at 35 GeV. © 1988 Springer-Verlag.